Beach resort development : case comparison between Pattaya and Jomtien. - Goh, Jolene Siok Yen. (2008)
The project focuses mainly on beach resort development in Pattaya and Jomtien, located on adjacent bays in Thailand. The execution of this research is motivated by the lack of related studies done in this region. Collective changes of the two beach resort are identified.